Effects of (S)-ketamine on depression-like behaviors in a chronic variable stress model: a role of brain lipidome - Zhou, Cuihong; Zhao, Xinxin; Ma, Xinxu; Ma, Hongzhe; Li, Rui; Hu, Guangtao; Wang, Huaning; Peng, Zhengwu; Cai, Min (Frontiers in Cellular Neuroscience, 2023)
Introduction: Compelling evidence indicates that a single sub-anesthetic dose of (S)-ketamine elicits rapid and robust antidepressant effects. However, the underlying mechanisms behind the antidepressant effects of (S)-ketamine remain unclear. Methods: Here, using a chronic variable stress (CVS) model in mice, we analyzed changes inthe lipid compositions of the hippocampus and prefrontal cortex (PFC) with a mass spectrometry-based lipidomic approach. Results: Similar to previous research outcomes, the current study also showed that (S)-ketamine reversed depressive-like behaviors in mice produced by CVS procedures. Moreover, CVS induced changes inthe lipid compositions of the hippocampus and PFC, notably in the contents of sphingolipids, glycerolipids, and fatty acyls. With the administration of (S)-ketamine, CVS-induced lipid disturbances were partially normalized, particularly in the hippocampus. Conclusion: Altogether, our results indicated that (S)-ketamine could rescue CVS-induced depressive-like behaviors in mice through region-specific modulation of the brain lipidome, contributing to the understanding of (S)-ketamine’s antidepressant effects.